Formation of Main Directions of Bolsheviks’ Cooperative Policy in Civil War and “War Communism” - A. V. Chichulin (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The relevance of the study is determined by insufficient exploration of the problem of the formation of the cooperative policy of the Bolsheviks in the difficult conditions of finding ways of building fundamentally new social, political and economic structure of Russia. The complex and contradictory process of forming a cooperative policy of central authorities and top officials of the state is examined. The question is raised about the strategy and tactics of cooperative policy of the Soviet government in the first years after the revolution. Special attention is paid to the identification of key areas of cooperative politics in the civil war and “war communism.” Key factors that influenced the position of various authorities in determining their relationship to the societies are established. The main priorities in the implementation of the cooperative policy are identified. The characteristics of cooperative policy implementation by the authorities are examined. The author comes to the conclusion that in the first months of Soviet power its actions gradually manifested two main directions in the formation of a cooperative policy. The first direction was characterized by the involvement of cooperative workers aimed at collaboration and the gradual transformation of societies in a form that would meet the ideological views of the Bolsheviks. The second movement is distinguished by the pursuit of power to capture the cooperation by administrative means, forcing it to fulfill the state order. Subsequently (over the entire study period), these two directions interacted with each other, forming in their unity cooperative policy which, in turn, was a part of the government’s economic policy.